Risks to Privacy v. Risks to Public Safety, a Dilemma to be overcome in the (Digital) Risk Society. Comments on the partially dissenting vote of Mr Justice Pinto De Albuquerque in the case of Big Brother Watch And Others v. The United Kingdom - MARQUESINI CHIAVONE, Tayrone (Revista Jurídica Portucalense, 2024)
The article examines the dilemma between privacy and public security in the context of the Big Brother Watch v. United Kingdom case, viewed through Ulrich Beck's concept of the Digital Risk Society. It explores the transition to a Digital Risk Society, highlighting challenges posed by the Fourth Industrial Revolution and increased digital surveillance. The article discusses the "riskification" process of privacy and data protection, emphasizing the regulatory shift from informational self-determination to risk management. It analyzes Judge Pinto Albuquerque's opinion, underlining his concerns about the proportionality and necessity of mass interceptions and the dangers of an electronic "Big Brother." The article concludes by pointing out the need for a more technical and conscious balance between privacy and security, stressing the importance of raising public awareness about surveillance risks.